Design of self-powered energy harvesting circuits for thermo-electric generator based applications - Abhik Das (2017)
With the advent of highly sophisticated electronic devices that are used in body-wearable applications implanted inside the bodies, demand for portable electronics for smart sensors, actuators, as well as other multi-media handsets are rising. In addition, with the ease of portability arises the increased research and commercialization of Internet-of-Things (loT). Therefore, the new ultra-low power circuit techniques are also evolving constantly that focus on improving the circuit's energy efficiency and reducing energy losses in the devices. The energy processing and interface circuits along with its power delivery system to the load or applications become highly critical in terms of energy, cost and size. With such systems, arise the new battery-less self-powered devices used for such micro-scale applications via microenergy harvesting from the ambient energy sources as alternate energy sources, instead of the external electrical supplies. This is a move towards self-sustainability, portability, minimizing cost and energy headroom. In this research, we have focused on such systems that harvest the DC form of energy, essentially the thermal form . The first part of this work focuses on the development of a startup circuit from micro-scale thermal energy sources that would self-startup with the aid of output information feedback. It provides a strong reset pulse signal to turn on and off a switch once, to perform a charge transfer cycle via a primary boost converter. It employs a charge-pump to provide an intermediate high voltage at the supply of the switch of the reset-based starter to enable the afore-mentioned action. The circuit is simulated in 65nm CMOS technology node. The converter is designed to regulate its output voltage at 1 V, storing it in the on-chip storage capacitor. A fast startup time of 35j..ls is obtained at 290m V input voltage. The maximum boost converter efficiency is recorded at 77%. The loss mechanisms in the startup are analyzed in details and possible shortcomings with future solutions are also discussed. The second part of the thesis identifies problems faced by the existing state-of-the-art startup circuits as well as the first proposed architecture. It proposes a starter for modern Thermo-Electric-Generator (TEG) based harvesters that have high electrical series resistances. The starter consists of a novel Power-onReset (PoR) circuit that uses the high electrical series resistance of the TEG to generate a controlled-train of pulses that can drive a charge-pump to an intermediate higher voltage. The harvester test results are shown in detail, which is fabricated in 65nm CMOS technology node. It can startup from 220mV at a TEG series resistance of350n, with a minimum possible startup voltage of 170m V at 700. The starter is equipped with an automatic disabling property that ensures that the quiescent leakage losses in the starter is minimized at steady-state. The harvesting interface circuit achieves a maximum conversion efficiency of 76%. The third and the final work identifies limitations with the second reported work, to propose a PoR circuit that is completely isolated from the main boost converter or the circuit components associated with the steady-state. The charge-pump is used here, to boost voltage swing of the finite-length clock signals from the PoR's output, and present its output at the gate of a low-side nMOS of a primary boost converter. The circuit achieves an improved startup functionality and a minimum startup voltage of 150m Vat a resistance of 450Q. The harvesting system can harvest from a maximum series resistance of 600n. It can achieve a maximum conversion efficiency of 78% in steady-state.